The Influence Chief Financial Officer, Profitabiltas, Leverage and Audit Committe on Tax Avoidance With Firm Size as a Control Variable - Okka Bekti Dwi Anggara; Kautsar Riza Salman (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
The state gets its money from taxes, although taxes are a burden that reduces the income of businesses. To minimize tax costs, businesses use tax avoidance strategies. Tax evasion is a deliberate attempt by a company to reduce its tax liability through legal means or through strategies and activities that occupy a gray area. The purpose of this research is to collect empirical evidence regarding the effect of Chief Financial Officer, profitability, leverage, and audit committee on tax evasion with firm size as a control variable. The approach used in this research is a quantitative approach. The research sample was 30 mining companies listed on the IDX in the 2019-2021 period, so 90 observations were used. The data analysis technique used is multiple linear regression. This study finds that tax avoidance is not affected by Chief Financial Officer. Likewise, the results are the same using the control variable, namely firm size, Chief Financial Officer also does not have a significant effect on tax avoidance. Conversely, profitability with or without control variables has a positive and significant effect on tax evasion. Different results on leverage, where leverage with or without a control variable has no effect on tax evasion. The audit committee also found no effect on tax evasion with or without control variables.